Bucardium grateloupianum n. sp. from the Lower Miocene of Aquitaine with taxonomic comments on some fossil species from Europe (Bivalvia, Cardiidae) - La Perna, R. (Zootaxa, 2016)
The genus Bucardium J. E. Gray, 1853 has been widely used in the past literature, either for living and fossil cardiids, but only a single species was known, its type species B. ringens (Bruguière, 1789), living in the tropical waters of West Africa. Another species, from the Lower Miocene of the Aquitaine Basin, turned out to be undescribed, though known since the 19th century. It is herein described as Bucardium grateloupianum n. sp. The genus seems to have always had a low diversity and a tropical distribution. Its disappearance in Europe coincides with the general cooling trend recorded after the Middle Miocene. Several poorly known cardiids from the Lower-Middle Miocene of France and Austria and from the Upper Oligocene of Hungary show closer morphological affinities with the living Cardium indicum Lamarck, 1819, rather than with the genus Bucardium or with Cardium costatum Linnaeus, 1758, the type species of Cardium Linnaeus, 1758. These affinities suggest the need of a systematic reappraisal of the living and fossil species currently assigned to Cardium.